2007
DOI: 10.1111/j.1750-3841.2006.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Potassium Lactate and Sodium Diacetate in Combination with Irradiation to Control Listeria monocytogenes on Frankfurters

Abstract: The use of antimicrobial ingredients in combination with irradiation is an effective antilisterial intervention strategy for ready-to-eat meat products. Microbial safety was evaluated for frankfurters formulated with 0% or 3% added potassium lactate/sodium diacetate solution and inoculated with Listeria monocytogenes before or after treatment with irradiation (0, 1.8, or 2.6 kGy). Frankfurters were stored aerobically or vacuum packaged and L. monocytogenes counts and APCs were determined while refrigerated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…For the UV-C-treated frankfurters, an initial drop in viable pathogens was observed, followed by a recovery during the 12 week storage period for L. monocytogenes and S. aureus. Similar results were observed for L. monocytogenes and S. aureus inoculated into sausages and frankfurters containing SDA and PL when sublethal doses of ionizing radiation were applied, followed by storage at 10C (Seman et al 2002;Sommers et al 2003;Sommers and Boyd 2006;Knight et al 2007). The use of SDA, PL and LAE in combination resulted in decreases for all three pathogens; however, the cfu/g of L. monocytogenes and S. aureus leveled off between weeks 8 and 12.…”
Section: Foodborne Pathogens On Frankfurterssupporting
confidence: 77%
“…For the UV-C-treated frankfurters, an initial drop in viable pathogens was observed, followed by a recovery during the 12 week storage period for L. monocytogenes and S. aureus. Similar results were observed for L. monocytogenes and S. aureus inoculated into sausages and frankfurters containing SDA and PL when sublethal doses of ionizing radiation were applied, followed by storage at 10C (Seman et al 2002;Sommers et al 2003;Sommers and Boyd 2006;Knight et al 2007). The use of SDA, PL and LAE in combination resulted in decreases for all three pathogens; however, the cfu/g of L. monocytogenes and S. aureus leveled off between weeks 8 and 12.…”
Section: Foodborne Pathogens On Frankfurterssupporting
confidence: 77%
“…Porto et al (2002) indicated that the use of 2 or 3% potassium lactate as an ingredient had a listeriostatic effect on frankfurters inoculated with either 20 or 500 cfu L. monocytogenes over a 90-d vacuum storage period at 4°C. Knight et al (2007) combined sodium lactate and diacetate treatment with irradiation of frankfurters that resulted in retarding the growth of Listeria from wk 6 to 8 during the 8-wk storage period.…”
Section: Introductionmentioning
confidence: 99%
“…The antilisterial efficacy of these acids is affected by many factors such as pH, water activity, nitrite, salt content, storage conditions, and other inhibitor components (Legan, Seman, Milkowski, Hirschey, & Vandeven, 2004;Samelis et al, 2003;Seman, Borger, Meyer, Hall, & Milkowski, 2002). Improvement of antilisterial activity has been reported by mixing these organic acids with other inhibitors including hop acids (Barmpalia et al, 2004;Knight, Castillo, Maxim, Keeton, & Miller, 2007;Shen & Sofos, 2008;Zhu, Mendonca, Ismail, & Ahn, 2009). …”
Section: Introductionmentioning
confidence: 95%